Investigating the factors affecting e-procurement adoption in supply chain performance: An empirical study on Malaysia manufacturing industry - Lee, Khai Loon; Amin, Agnessia Jeba; M. Alzoubi, Haitham; Alshurideh, Muhammad; El Khatib, Mounir; Joghee, Shanmugan; Nair, Kiran (Growing Science Ltd., 2024)
Global business is getting more and more cutthroat. Digital technology plays a significant role in giving companies a competitive advantage and improving the effectiveness of corporate processes. The Malaysian government has advanced by implementing e-government to use digital technologies to improve operations. In line with the objective of Malaysia’s government, this study examines the impact of e-procurement adoption and e-procurement determinants on supply chain performance among Malaysian manufacturing companies. Using a quantitative research design with an online survey questionnaire, 99 responses from manufacturers listed in the Federation of Malaysian Manufacturers directory were obtained, representing 19.41% of the response rates. It fulfilled the minimum sample size of 92, and the data were examined using PLS-SEM. A total of 13 hypotheses are supported, accepted hypotheses one and two in which top management support and information communication technology infrastructure do not directly affect supply chain management. Besides, the findings prove this study's mediating effect on e-procurement adoption. It indicates that most Malaysian manufacturing companies have embraced e-procurement to support their supply chain operations.